Peningkatkan Hasil Belajar Siswa Kelas 8 SMPN 5 Balikpapan Tentang Sakramen Ekaristi dengan Model Problem Based Learning - Maria Emakulata Mei (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This research aims to improve the learning outcomes of eighth-grade students at SMPN 5 Balikpapan in the 2024/2024 academic year in Catholic Religious Education and Character Building through the implementation of the Problem Based Learning (PBL) model. The research type is Classroom Action Research (CAR) conducted in two cycles with two meetings in each cycle. Each cycle consisted of 4 stages: planning, action implementation, observation, and reflection. The first and second cycles discussed the material of the Sacrament of the Eucharist. The subjects in this research were six Catholic eighth-grade students at SMPN 5 Balikpapan in the 2024-2025 academic year. The data collection techniques used were tests and observation. The research results showed that the implementation of the Problem Based Learning (PBL) model could improve the learning outcomes of eighth-grade students from cycle 1 to cycle 2, namely from 70 in Cycle 1 to 80.83 in Cycle 2. The conclusion of this research is that the implementation of the Problem Based Learning (PBL) model assisted by Audio-Visual Media can improve the learning outcomes of Catholic Religious Education and Character Building for eighth-grade students at SMPN 5 Balikpapan in the 2024/2025 academic year.